Lead (Pb) Levels in Liver and Muscle Tissues of Atlantic Bluefin Tuna (Thunnus thynnus Linnaeus, 1758) - KAYHAN, FİGEN ESİN (FOUNDATION ENVIRONMENTAL PROTECTION & RESEARCH-FEPR, 2010)
In this study, lead (Pb) levels were investigated in liver and muscle tissues of Atlantic bluefin tuna (Thunnus thynnus) caught in the Gulf of Antalya in May-June 2007. Atomic absorption spectrophoto-meter (AAS) was used to determine lead mean levels in tissues. Lead levels were determined at levels of maximum 1.10 ppm, minimum 0.20 ppm in liver and maximum 1.18 ppm, minimum 0.18 ppm in muscle tissue. Levels of lead are below the acceptable limits in almost all tissues.
Keywords: Bluefin tuna; Gulf of Antalya; heavy metal; lead; pollution; Thunnus thynnus; HEAVY-METALS; CD; FISH; CAUGHT; CU; SEA; BIOACCUMULATION; ACCUMULATION; PROFILE; MULLET